2020
DOI: 10.3390/app10248799
|View full text |Cite
|
Sign up to set email alerts
|

An Intelligent Controlling Method for Battery Lifetime Increment Using State of Charge Estimation in PV-Battery Hybrid System

Abstract: In a photovoltaic (PV)-battery integrated system, the battery undergoes frequent charging and discharging cycles that reduces its operational life and affects its performance considerably. As such, an intelligent power control approach for a PV-battery standalone system is proposed in this paper to improve the reliability of the battery along its operational life. The proposed control strategy works in two regulatory modes: maximum power point tracking (MPPT) mode and battery management system (BMS) mode. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 50 publications
(44 reference statements)
0
9
0
Order By: Relevance
“…Therefore, both the available recourses are disconnected from the connected load. In another similar recent research [9], the intelligent power control shown in Figure 3 was developed to improve battery reliability and operational life. The power control operates in two control modes: 1) MPPT mode and 2) Battery Management System (BMS) mode.…”
Section: A Study Of Selected Battery Charging/discharging Management Methodologiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, both the available recourses are disconnected from the connected load. In another similar recent research [9], the intelligent power control shown in Figure 3 was developed to improve battery reliability and operational life. The power control operates in two control modes: 1) MPPT mode and 2) Battery Management System (BMS) mode.…”
Section: A Study Of Selected Battery Charging/discharging Management Methodologiesmentioning
confidence: 99%
“…Renewable energy systems are known as highly dependent systems to battery storages, which allows them to store the produced energy into the connected batteries [1][2][3] and optimize the battery charging-discharging operation [4,5]. Looking at the gaining popularity of the renewable energy systems, especially the microgrid renewable energy systems, battery storage charging and discharging [1,[6][7][8][9][10][11] are equally crucial for the renewable energy system in both islanded and non-islanded modes. Both modes need to ensure the reliability of the output energy with little to no disruption to the connected load during the operation hours [12].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The proposed method can also be used in renewable energy dependent devices as well as energy conversion systems [42][43][44][45][46][47][48][49][50]. It can also be adapted to monitor the condition of critical high voltage assets, power converters, and various flexible ac transmission system devices [51][52][53][54].…”
Section: Ishdb Tested With Iot Implementationmentioning
confidence: 99%